Difficulty in Anglo-American poetry: a linguistic and empirical perspective - Castiglione, Davide (2016)
This project sets out to develop a model for a study of difficulty in poetry as systematic and nuanced as possible. In doing so, it endeavours to make a significant theoretical and practical contribution to the fields of stylistics, poetics and literary theory. Throughout the twentieth century, the notion of difficulty in poetry has never ceased to interest linguists, literary theorists, psychologists and researchers in education. The popularity of the notion among non-specialist is equally significant, as it is not uncommon for readers to justify their lack of interest in poetry on the grounds of its supposed difficulty. Notwithstanding this, the dynamics of text-reader interaction – the defining trait of difficulty, as argued in Chapter 1 – remains notably underexplored. This thesis addresses this gap in the literature by (a) providing a psychologically plausible and linguistically sound account of difficulty; and by (b) unifying under a coherent framework the insights offered by a large body of materials – from critical readings of literary works to anecdotal evidence, from psychological models of comprehension to controlled psycholinguistic experiments.